Successful Treatment of Intracranial Hemorrhage with Recombinant Activated Factor VII in a Patient with Newly Diagnosed Acute Myeloid Leukemia: A Case Report and Review of the Literature - Pemmaraju, Naveen; Sasaki, Koji; Johnson, Daniel; Daver, Naval; Afshar-Kharghan, Vahid; Chen, Merry; Ahmed, Sairah; Colen, Rivka R.; Kwon, Michael; Huh, Yang; Borthakur, Gautam (Frontiers in Oncology, 2015)
Intracranial hemorrhage (ICH) is a common complication in acute myeloid leukemia (AML) patients with an incidence rate of 6.3% [1]. Bleeding disorders related to disseminated intravascular coagulation (DIC) are common complications in AML cases [2]. Recombinant activated Factor VII (rFVIIa [NovoSeven®]) is approved for the treatment of bleeding complications with FVIII or FIX inhibitors in patients with congenital FVII deficiency. Use of rFVIIa for the treatment of acute hemorrhage in patients without hemophilia has been successful [3,4]. Herein, we describe the successful use of rFVIIa in a patient with acute ICH in the setting of newly diagnosed AML.